A combination of FTIR and DFT methods to study the structure and interaction properties of TSILs and DMSO mixtures. (April 2019) - Zheng, Yan-Zhen; Shen, Zhi-Rong; Zhou, Yu; Guo, Rui; Chen, Da-Fu
Highlights: Hydrogen-bonding interaction is the main cause that induces the original IR spectra change of v s (C–D). The hydrogen-bonds between water and TSILs are the closed shell interaction, electrostatic dominant and weak strength. The excess spectra can help the deconvolution of the original infrared spectra. A number of species in the TSILs–DMSO‑ d 6 mixtures were identified from the deconvolution results. Abstract: In most practical applications, ionic liquids (ILs) are used in mixtures with molecular solvents to reduce the high viscosity of neat ILs, which greatly hinder the practical handling and various transport processes. Knowledge of the structure and interaction properties of ILs–co-solvent mixtures is necessary as they represent the basis for biological and chemical process. In this work, the structure and interaction properties of three task-specific ionic liquids (TSILs) and dimethylsulfoxide (DMSO) binary mixtures were studied by applying Fourier transform infrared spectroscopy (FTIR) and density functional theory (DFT) methods. The C–D systematic stretching vibrational region of DMSO‑ d 6 was closely examined. DMSO‑ d 6 was found to form a relatively stable hydrogen-bonding complex in three binary mixtures. The weak strength hydrogen-bonds between DMSO‑ d 6 and TSILs are the closed shell and electrostatic dominant interactions. With the help of excess infrared spectroscopy and quantum chemical calculations, a number of species in three binary mixtures were identified, namely, ion cluster–DMSO‑ d 6, ion pair–DMSO‑ d 6, cation–DMSO‑ d 6, and DMSO‑ d 6 self-association dimer. At x (DMSO‑ d 6 ) > 0.9, the three TSILs mainly exist in the form of individual cations and anions. At 0.8 > x (DMSO‑ d 6 ) > 0.7, the TSILs are mainly in the form of ionic pairs. When x (DMSO‑ d 6 ) < 0.6, the TSILs mainly exist in the form of ion clusters.